CSR Activities of the Chemical Company – a Case Study from Plastic Industry - Vávra, Jan; Bednaříková, Marie; Munzarová, Simona; Procházková, Klára (Česká společnost průmyslové chemie, 2017)
Concept of corporate social responsibility requires performing many activities from different areas. Companies solve environmental, social, philanthropic, ethical and economic tasks of company’s production processes and all of them contribute notably to corporate sustainable development. Many chemical companies considered CSR activities of company’s production processes as important tool for strengthening relationship with key stakeholders; especially with workers, consumers, local communities, and other shareholders and the level of CSR activities must be continuously supervised, developed, improved and communicated. The contribution deals with the overall level of realized CSR activities of chemical company. The main objective is to determine and summarize all CSR related activities to verify responsible approach of corporate management to key stakeholders as well as to express company’s contribution to sustainable development, sustainable production and consumption. Scope and focus of particular CSR activities will be closely described and discussed.
Činnosti CSR v chemickém podniku – případová studie z plastikářského průmyslu
Keywords: Corporate social responsibility; CSR activities; plastic industry; Společenská odpovědnost firem; CSR činnosti; plastikářský průmysl